Characterization and modeling of mechanical behavior of single crystal titanium deformed by split-Hopkinson pressure bar. (July 2016) - Morrow, B.M.; Lebensohn, R.A.; Trujillo, C.P.; Martinez, D.T.; Addessio, F.L.; Bronkhorst, C.A.; Lookman, T.; Cerreta, E.K.
Abstract: Single crystal titanium samples were dynamically loaded using split-Hopkinson pressure bar (SHPB) and the resulting microstructures were examined. Characterization of the twins and dislocations present in the microstructure was conducted to understand the pathway for observed mechanical behavior. Electron backscatter diffraction (EBSD) was used to measure textures and quantify twinning. Microstructures were profusely twinned after loading, and twin variants and corresponding textures were different as a function of initial orientation. Focused ion beam (FIB) foils were created to analyze dislocation content using transmission electron microscopy (TEM). Large amounts of dislocations were present, indicating that plasticity was achieved through slip and twinning together. Viscoplastic self-consistent (VPSC) modeling was used to confirm the complex order of operations during deformation. The activation of different mechanisms was highly dependent upon crystal orientation. For [0001] and [ 10 1 ¯ 1 ] -oriented crystals, compressive twinning was observed, followed by secondary tensile twinning. Dislocations, though prevalent in the microstructure, contributed to final texture far less than twinning. Graphical abstract: Highlights: Dynamic loading of single crystal titanium was performed. Complex microstructures due to twins and dislocations were measured post-mortem. Orientation affects active mechanisms which control hardening response.